Patients with chronic hepatitis B under nucleos(t)ide analog therapy with Omicron BA.5 infection: A retrospective study in South China - Peipei Wang; Junjian Chen; Dabiao Chen; Ziying Lei; Zhishuo Mo; Ying Zhang (Liver Research)
Background and aims: Clinical data regarding patients with chronic hepatitis B (CHB) after Omicron BA.5 infection are currently limited. This study aimed to assess the clinical characteristics of patients with CHB and Omicron BA.5 infection in South China. Methods: This retrospective study was conducted from January to March 2023 in a cohort of 485 healthy individuals and 553 patients with CHB. Clinical features, encompassing COVID-19-related symptoms, levels of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies, vaccination status, liver functions, and virological markers of hepatitis B virus (HBV) infection were measured. Results: COVID-19-related symptom patterns were similar in both groups, except for fever, which was notably less prevalent (85.4% vs. 90.4%, P = 0.047) among patients with CHB who experienced a significantly shorter duration of fever (median 2.2 (25th–75th percentile, 1.0–3.0) days vs. 2.3 (1.0–3.0) days, P = 0.048) and a shorter time for symptom relief (9.2 (5.0–14.0) vs. 11.1 (5.0–14.0) days, P = 0.015). The levels of SARS-CoV-2 antibodies were comparable between the two groups but increased after booster vaccinations. In patients with CHB, globulin (GLB) and hepatitis B envelope antibody levels were significantly increased after Omicron BA.5 infection, regardless of nucleos(t)ide analog regimens comparing entecavir (ETV) with tenofovir (TFV). Patients with CHB treated with TFV had significantly higher levels of SARS-CoV-2 antibodies than those treated with ETV (1065.1 (346.9–1188.5) COI vs. 765.5 (24.5–1119.1) COI, P = 0.025). Conclusions: No significant exacerbation of COVID-19 symptoms was observed in conjunction with the efficacy of COVID-19 booster vaccinations. There were no notable alterations in liver functions except for GLB. HBV reactivation, as evidenced by increased HBV DNA, was observed among patients with CHB after Omicron BA.5 infection. These changes were not affected by ETV versus TFV administration; however, TFV resulted in a significant increase in SARS-CoV-2 antibody levels. Further studies are required to improve care and therapeutics for patients with CHB who contracted COVID-19.